The Role of the Village Government in the Development of Tourism Objects as Economic Potential in Sarani Matani Village - Gugule, Hamdi; Runtu, Nensy Brigita; Salem, Veronike E.T.; Mesra, Romi; Hasrin, Awaluddin (Technium Social Sciences Journal, 2023)
The issue in this study is the village government’s involvement in supervising the development of dam tourist objects. The purpose of this research is to assess the village government’s participation in establishing dam tourist objects as an economic potential in Sarani Matani Village. This study used a qualitative descriptive technique to collect data through interviews, observation, and recording. According to the findings, adding tourism objects and amenities such as parking lots, enhancing infrastructure and public facilities, adding facilities and infrastructure such as water bicycles, etc., restaurants or cafés, and offering souvenirs/souvenirs are all beneficial. whereas the village government’s activities include: developing the potential of tourism assets held by the community, promoting these tourist objects through electronic and print media, or from one individual to another, construct all of the amenities required by visitors on activity vacations, and increase the capacity of human resources (HR) to provide good service to tourists.